Ablative stereotactic radiotherapy for oligometastatic colorectal cancer: Systematic review. (September 2018) - Kobiela, J.; Spychalski, P.; Marvaso, G.; Ciardo, D.; Dell'Acqua, V.; Kraja, F.; Błażyńska-Spychalska, A.; Łachiński, A.J.; Surgo, A.; Glynne-Jones, R.; Jereczek-Fossa, B.A.
Highlights: SBRT is a novel and promising modality in treatment of oligometastatic CRC with local control up to 92% at 2 years. Higher number of metastases seems to be associated with worse prognosis, what suggests that the paradigm on oligometastatic state is correct. Toxicities reported by authors were very low - 11 out of 15 authors reported toxicities none grade≥3. Dose escalation seems to enable achieving better prognosis – higher BED10 seems to be associated with higher local control. There is an urge for creating a unified reporting system for results on efficacy of SBRT in treating metastases. Abstract: Background: SBRT is a novel modality in treatment for oligometastatic colorectal cancer. We aimed to perform a systematic review of results of SBRT in maintaining LC (local control) for CRC liver and lung oligometastases. Materials and methods: The review was performed according to PRISMA and PICO guidelines. Database search using keywords: stereotactic, colon, colorectal, cancer, sbrt, sabr returned 457 results. 15 were included in the study. Only cohorts with CRC histology and reported LC were included. Results: For liver LC rates ranged from 50% to 100% after 1 year and 32% to 91% after 2 years. BED range 40.5–262.5 Gy (Gray). For lung LC rates ranged from 62% to 92% after 1 one year and from 53% to 92% after 2 years. BED range 51.3–262.5 Gy. Conclusions: SBRT of oligometastatic CRC offers high LC with low morbidity and toxicity. It requires more observational studies and randomized trials but available data on clinical efficacy is promising, however not yet matured.